Storage Methods of Complex RNA Viruses - Varianytsia, Viktoriya V.; Vysekantsev, Igor P. (Problems of Cryobiology and Cryomedicine, 2017)
The review describes the development of methods for the long-term storage of complex RNA viruses. The need of such an activity is stipulated by a wide spreading of infectious diseases caused by these viruses and rising number of the studies dealing with developing the drugs for immune prophylaxis and therapy. Among other things the technology for these drugs production involves the long-term storage of viruses. This includes freeze-drying and storage at temperatures below0°C. However, to date no generally accepted approaches exist in terms of composition of protective media for either freeze-drying or low-temperature storage of viruses. For this purpose, one uses the numerous additives and combinations of various sugars, polyhydric alcohols, animal proteins, chemical compounds. Storage of frozen-dried viruses is performed at either 4 or –20°C, and in case of a frozen state it ranges from –60 to –85°C, that is stipulated by the availability of freezing chambers providing these temperatures, and high survival of viruses from different families. Probl Cryobiol Cryomed 2017; 27(4): 287–295